THE EFFECT OF DIGITAL MARKETING ON PROMOTION AND MARKETING PERFORMANCE IN MICRO ENTERPRISES IN KALIMANTAN - Putra, Sinar Dharmayana; Michael Ricky Sondak; Erwin Parega; Sean Michael Owen Wijaya; Valencia Fenessa Turisno (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2025)
Digital marketing has become a key pillar in modern business strategies, including for micro-enterprises in Kalimantan. This study aims to analyze the impact of digital marketing on the marketing performance of micro-enterprises in the region. By utilizing quantitative and qualitative data, this study found that the adoption of digital marketing increases visibility, operational efficiency, and customer engagement. In addition, this study also highlights the challenges faced by micro-enterprises in implementing digital marketing strategies. The results of this study are expected to provide insights for stakeholders and business actors in optimizing the use of digital marketing.